Analysis of the Role of Heat Shock Protein (Hsp) Molecular Chaperones in Polyglutamine Disease - Chai, Yaohui (J Neurosci, 1999)
Polyglutamine (polygln) diseases are a group of inherited neurodegenerative disorders characterized by protein misfolding and aggregation. Here, we investigate the role in polygln disease of heat shock proteins (Hsps), the major class of molecular chaperones responsible for modulating protein folding in the cell. In transfected COS7 and PC12 neural cells, we show that Hsp40 and Hsp70 chaperones localize to intranuclear aggregates formed by either mutant ataxin-3, the disease protein in spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD), or an unrelated green fluorescent protein fusion protein containing expanded polygln. We further demonstrate that expression of expanded polygln protein elicits a stress response in cells as manifested by marked induction of Hsp70. Studies of SCA3/MJD disease brain confirm these findings, showing localization of Hsp40 and, less commonly, Hsp70 chaperones to intranuclear ataxin-3 aggregates. In transfected cells, overexpression of either of two Hsp40 chaperones, the DNAJ protein homologs HDJ-1 and HDJ-2, suppresses aggregation of truncated or full-length mutant ataxin-3. Finally, we extend these studies to a PC12 neural model of polygln toxicity in which we demonstrate that overexpression of HDJ-1 suppresses polygln aggregation with a parallel decrease in toxicity. These results suggest that expanded polygln protein induces a stress response and that specific molecular chaperones may aid the handling of misfolded or aggregated polygln protein in neurons. This study has therapeutic implications because it suggests that efforts to increase chaperone activity may prove beneficial in this class of diseases.